Mapping and impact of seasonal forest fires on vegetation types, soil dynamics, and tree mortality in the forest ecosystem of Uttarakhand Himalaya - Himanshu Bargali; Dinesh Bhatt; Rakesh Chandra Sundriyal; Virendra Prasad Uniyal (Landscape Online)
This study investigates forest fire dynamics and their implications for management in the Uttarakhand Himalaya region. Utilizing remote sensing analysis, field surveys, and socio-economic assessments, the research aims to understand the spatial and temporal patterns of fires, assess their impact on vegetation, soil properties, and biodiversity, and propose effective management strategies. Results reveal a significant increase in fire frequency and severity, with a 25% rise in fire occurrences observed over the past decade. High-intensity fires caused extensive damage to vegetation, with a 40% reduction in tree density observed in severely affected areas. Soil organic matter loss due to fires averages at 15%, threatening ecosystem health and resilience. However, opportunities for fire management exist, including prescribed burning and community-based prevention programs. Policy recommendations emphasize the importance of integrating ecological and socio-economic perspectives into fire management strategies to promote ecosystem resilience and community adaptation. This study contributes valuable insights for policymakers, forest managers, and local communities to develop science-based fire management policies and practices, ultimately fostering sustainable forest management and fire risk reduction in the Uttarakhand Himalaya region.